Performance Analysis of a Semi-Automatic Roasting Machine Through Modification of a Thermocontroller Heating System - Moh Bagus Rialdo (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The roasting process in the food processing industry requires stable temperature control to produce consistent product quality. However, conventional roasting machines generally have limitations in heat distribution and temperature stability, which affect energy efficiency and the quality of the final product. Therefore, this study aims to analyze the performance of a semi-automatic roasting machine through the modification of a thermocontroller-based heating system using a thermocouple sensor. The research employed an engineering design method, including the design, fabrication, and testing of the machine at temperature variations ranging from 160°C to 300°C. The evaluated parameters included temperature stability, roasting time, and product quality. The results showed that the implementation of the thermocouple significantly reduced temperature fluctuations to ±1°C–±2%, shortened the roasting time, and improved the consistency of product quality with an average score of 4–4.5. In conclusion, the thermocontroller-based heating system effectively enhances the performance of the roasting machine and has strong potential for application in small and medium enterprises.